The Chaplain as Translator - Macritchie, Iain (Journal of religion and health, 2001)
The Chaplain finds herself continually in the position of the translator, having to move in the space between subject and object. This space Winnicott calls "Transitional," and Ulanov sees as particularly the domain of the clergy. The nature of these gaps is analysed, especially with respect to Chaplaincy and the work of the individual Chaplain. Various kinds of transitional space are examined, and the challenges facing the Chaplain in these situations are highlighted.